2016
DOI: 10.20307/nps.2016.22.2.77
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous HPLC Analysis of Three Flavonoids in the Extracts ofArtocarpus heterophyllusHeartwoods

Abstract: − A reversed-phase high-performance liquid chromatographic method is described for the simultaneous determination of three antibacterial flavonoids, artocarpanone, artocarpin, and cycloartocarpin in ethyl acetate extracts from Artocarpus heterophyllus heartwoods. Separation was achieved using a TSK-gel ODS-80Tm column (5 µm, 4.6 × 150 mm) at 25 o C with a gradient elution system of methanol and water as follows: 0-8 min, 60:40; 8-27 min, 80:20; 27-35 min, 60:40, v/v, at a flow rate of 1 mL/min, and a quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The percentage inhibition of the extract and artocarpin on chemotaxis, ROS production and MPO activity were relatively similar. Our previous study demonstrated that artocarpin was the major compound in A. heterophyllus extract, while ethyl acetate was the suitable solvent for extraction of this compound …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percentage inhibition of the extract and artocarpin on chemotaxis, ROS production and MPO activity were relatively similar. Our previous study demonstrated that artocarpin was the major compound in A. heterophyllus extract, while ethyl acetate was the suitable solvent for extraction of this compound …”
Section: Resultsmentioning
confidence: 99%
“…Our previous study demonstrated that artocarpin was the major compound in A. heterophyllus extract, while ethyl acetate was the suitable solvent for extraction of this compound. [23] Structure-activity analysis of the flavonoids on phagocytosis activity indicated that a saturation of the C-2 and C-3 in the C ring as well as 2 hydroxyl group in the B ring (C-2 0 and C-4 0 ) and a methoxy group in the A ring of artocarpanone might contribute towards its inhibitory activity, particularly on ROS production and chemotaxis activity of phagocytes. It has been shown that saturated C-2 and C-3 bond in the C ring, increasing number of -OH in the B ring, as well as one methoxy substitution in the A ring of flavonoid compound increased superoxide scavenging activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4.6 × 250 mm, 5 μm column). The analysis was performed according to Septama and Panichayupakaranant (2016) with modification of the adjusted mobile phase. A mobile phase was prepared that consisted of methanol and water (85% methanol and 15% deionized water), at a flow rate of 1 mL/min.…”
Section: Quantification Of Compounds Bioactive Compound By Hplcmentioning
confidence: 99%